F. Xavier Vila & Vanessa Bretxa (eds.) «Language Policy in Higher Education. The Case of Medium-Sized Languages», Bristol, Multilingual Matters, 2015, 218 pp. - Casesnoves Ferrer, Raquel (Caplletra. Revista Internacional de Filologia, 2016)
Ressenya sobre el llibre de F. Xavier Vila & Vanessa Bretxa (eds.) Language Policy in Higher Education. The Case of Medium-Sized Languages, Bristol, Multilingual Matters, 2015, 218 pp.